Strategic Control over Effective Use of Equity Capital Based on Indicators of the Derivative Balance Sheet - I. Tsyutsyak; A. Tsyutsyak (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article exposes essence of strategic control and highlights the need for its identification in the system of internal control. A methodology is developed to draw up a derivative balance sheet and use its data in the strategic control system. The study establishes a procedure for assessing quality of the strategic management decisions that are taken on the base of the analysis of derivative indicators.The study outcomes can be of use for practitioners and researchers investigating company's internal control, the teachers and students dealing with economics and management.